Drk1, a dimorphism histidine kinase, contributes to morphology, virulence, and stress adaptation in paracoccidioides brasiliensis - Marcos, Caroline Maria [UNESP] (2021)
P. brasiliensis is a thermally dimorphic fungus belonging to Paracoccidioides complex, causative of a systemic, endemic mycosis limited to Latin American countries. Signal transduc-tion pathways related to important aspects as surviving, proliferation according to the biological niches are linked to the fungal pathogenicity in many species, but its elucidation in P. brasiliensis remains poorly explored. As Drk1, a hybrid histidine kinase, plays regulators functions in other dimorphic fungi species, mainly in dimorphism and virulence, here we investigated its importance in P. brasilensis. We, therefore generated the respective recombinant protein, anti-PbDrk1 polyclonal antibody and a silenced strain. The Drk1 protein shows a random distribution including cell wall location that change its pattern during osmotic stress condition; moreover the P. brasiliensis treatment with anti-PbDrk1 antibody, which does not modify the fungus’s viability, resulted in decreased virulence in G. mellonella model and reduced interaction with pneumocytes. Down-regulating Pb-DRK1 yielded phenotypic alterations such as yeast cells with more elongated morphology, virulence attenuation in G. mellonella infection model, lower amount of chitin content, increased resistance to osmotic and cell wall stresses, and also caspofungin, and finally increased sensitivity to itraconazole. These observations highlight the importance of PbDrk1 to P. brasiliensis virulence, stress adaptation, morphology, and cell wall organization, and therefore it an interesting target that could help develop new antifungals.